PENATALAKSANAAN FISIOTERAPI PADA KASUS STROKE HEMIPARESE - Ni Kadek Ardya Shinta Alverina; Made Hendra Satria Nugraha; Kadek Arya Wiguna (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Stroke can occur at any age. Stroke is the second leading cause of death and the third leading cause of disability in the world. Stroke is caused by several factors, namely intrinsic and extrinsic factors. Stroke can cause muscle weakness, balance disorders, shoulder subluxation, limited ROM, spasticity or flaccidity and others. In this study, the problems found in clinical cases in the field were muscle weakness, spasticity, shoulder subluxation, limited ADL, balance and coordination disorders. Handling of the problems found in the field is with the principle of active muscle strengthening movements assisted by NMES modalities, the Bobath Concept to reduce spasticity, PNF Patterns with resistance techniques to improve coordination and muscle strength, Core Exercise to improve trunk control so as to improve balance, and the use of Kinesio Tapping to reduce shoulder subluxation. Based on the results of the intervention for 2x/week in 1 week, it showed good results in reducing shoulder subluxation and improving balance in stroke patients. Interestingly, patients expressed that they felt an increase in balance when using kinesio tapping compared to not using kinesio tapping. Keywords: Core exercise; Kinesio Tapping, Stroke